Infrared spectroscopy of chemically modified heparins. - Grant, D (1989)
Analysis by i.r. spectroscopy of natural and chemically modified heparins suggests that the N-sulphonate group of these polymers may vibrationally absorb radiation at two distinctly different frequencies. This property may reflect the existence of different conformational states important in the biological activities of the polymers. Examination of carboxylate- and N-acetyl-group absorbances of these polymers accords with the possibility that one of these polymer conformational states involves interaction between juxtaposed N-sulphonate and carboxylate groups. In heparin bearing large quantities of artificially introduced N-acetyl groups, an interaction between carboxylate and N-acetyl groups may also occur.